Designs, Systems, Scapegoats, and Business Cultures - Saariluoma, Pertti (Human Technology, 2009)
In November 2007, an event happened in Nokia that threatened the health of thousands of people. Now the Nokia in this story is not the world-known telecommunications corporation, but rather the little city that shares its name: a city in southwestern Finland from which a large rubber company operating there named itself. A century later, that company made a strategic shift in its product focus, and expanded its operations beyond the little city and even outside of Finland. To my knowledge, the Nokia company no longer has factories or offices in the city of Nokia, but this story about the city of Nokia remains an important lesson in human-technology interaction.